2014
DOI: 10.1016/j.envpol.2013.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Predicting nitrogen and acidity effects on long-term dynamics of dissolved organic matter

Abstract: Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner. Increases in dissolved organic carbon (DOC) fluxes may relate to changes in sulphur and nitrogen 29 pollution. We integrated existing models of vegetation growth and soil organic matter turnover, 30 acid-base dynamics, and organic matter mobility, to form the 'MADOC' model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 70 publications
1
32
0
Order By: Relevance
“…Observing differences that occur at different scales and between different processes has added to our knowledge concerning those factors that control DOC dynamics (Clark et al 2010). The development of models based on a mechanistic understanding has also helped to unify our understanding of processes (Futter et al 2007;Rowe et al 2014). In the present study we have shown that even apparently negligible differences in simulating present day conditions can lead to large uncertainties when projecting future catchment [DOC] and exports (Fig.…”
Section: Change In Hydroclimatic Regimesmentioning
confidence: 76%
“…Observing differences that occur at different scales and between different processes has added to our knowledge concerning those factors that control DOC dynamics (Clark et al 2010). The development of models based on a mechanistic understanding has also helped to unify our understanding of processes (Futter et al 2007;Rowe et al 2014). In the present study we have shown that even apparently negligible differences in simulating present day conditions can lead to large uncertainties when projecting future catchment [DOC] and exports (Fig.…”
Section: Change In Hydroclimatic Regimesmentioning
confidence: 76%
“…For example, it has been suggested that net primary productivity (NPP), and hence the supply of potentially soluble organic matter, is now higher than in pre-industrial times as a result of the accumulation of atmospherically deposited reactive nitrogen in these catchments (Rowe et al 2014;Tipping et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Some studies have linked the OC rise to recent changes in land-use practices, such as the drainage and burning of peatlands (18,19), or to changes in land cover (20). Other proposed explanations are the increase in atmospheric carbon dioxide levels (21) and the elevated atmospheric deposition of nitrogen (22,23), both of which support increased plant productivity.…”
mentioning
confidence: 99%